2023
DOI: 10.1002/poi3.338
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the potential of civil disagreement to decrease issue polarization in China

Abstract: With mass polarization becoming an increasingly urgent sociopolitical agenda in both established and emerging democracies, academics and policy‐makers have been racing to develop effective depolarizing approaches. While (semi‐)authoritarian nations have also been afflicted by social cleavage and a negative, incompatible and even radicalized discussion climate towards public policy and sociopolitical issues, polarization and related countermeasures in such contexts have thus far gained scarce academic attention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…Despite the presence of social divisions and a contentious, divergent and potentially radicalized discourse on public policy and socio-political issues in semi-authoritarian nations, there has been limited scholarly research on polarization and effective countermeasures in such contexts (Bail et al, 2018;Muise et al, 2022). Guan et al (2023) demonstrated the efficacy of public controversy as a virtue and prerequisite for mitigating extreme opinions. Additionally, Scherman et al (2022) highlighted the importance of political persuasion in promoting vibrant democracies and as a critical component of political campaigns.…”
Section: Political Democracymentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the presence of social divisions and a contentious, divergent and potentially radicalized discourse on public policy and socio-political issues in semi-authoritarian nations, there has been limited scholarly research on polarization and effective countermeasures in such contexts (Bail et al, 2018;Muise et al, 2022). Guan et al (2023) demonstrated the efficacy of public controversy as a virtue and prerequisite for mitigating extreme opinions. Additionally, Scherman et al (2022) highlighted the importance of political persuasion in promoting vibrant democracies and as a critical component of political campaigns.…”
Section: Political Democracymentioning
confidence: 99%
“…Potential research directions Psychology of cognitive biases on user perception (Andreotta et al, 2022;Barbera et al, 2015;Beck and Clark, 1997;De Zuniga et al, 2022;Lee, 2022;Messing and Westwood, 2012) User psychological profiles and perceptions of controversial issues Impact of selective exposure on polarization Emotional reactions to the event Cognitive de-biasing techniques development In-group and out-group affiliation Changes in user behavior Distorted view of reality, reinforcing stereotypes and deepening polarization Technical aspects of quantifying polarization (Barrett et al, 2021;Burgers et al, 2023;Grover et al, 2019;Lu et al, 2022;Modgil et al, 2021;Park, 2021;Tornberg, 2021) Influence of cognitive biases on people's reading and sharing behavior Fact-checking tools Polarization's impact on people's mental health Interventions to recognize and counteract biases Development and spreading of biases in digital communities AI and machine learning in studying bias-based polarization Inventions include mindfulness, cognitive behavioral therapy techniques, or metacognitive strategies Information system (IS) perspective on polarization (Allcott and Gentzkow, 2017, Au et al, 2021, Barfar, 2019Kaiser et al, 2022, Miller et al, 2022Vicario et al, 2019;Wang, 2015) Designing intelligent systems to mitigate polarization User interaction with personalized content The role of misinformation Longitudinal effects Evaluation of existing efforts The implications of decentralized social networks Comparative study across different platforms Management strategies on polarization (Feezell et al, 2021;Guan et al, 2023;Klein and Robison, 2019;Medaglia and Zhu, 2017) Reputation of organization in a polarized environment Education and media literacy Ethical considerations Crisis communication and response strategies for potential bias-based backlash Engagement management for balance among communities Internal communication and training to understand and recognize bias Content moderation and guidelines Source(s): Authors' own creation Table…”
Section: Perspectivesmentioning
confidence: 99%